Fluid flow simulation and permeability computation in deformed porous carbonate grainstones. (May 2018) - Zambrano, Miller; Tondi, Emanuele; Mancini, Lucia; Lanzafame, Gabriele; Trias, F. Xavier; Arzilli, Fabio; Materazzi, Marco; Torrieri, Stefano
Highlights: An MRT-LBM was used for obtaining viscosity-independent permeability in deformed carbonates. The influence of the pore-network morphology on the permeability was investigated. Fault core shows significant heterogeneity and permeability anisotropy in comparison to the host rock. Abstract: In deformed porous carbonates, the architecture of the pore network may be modified by deformation or diagenetic processes altering the permeability with respect to the pristine rock. The effects of the pore texture and morphology on permeability in porous rocks have been widely investigated due to the importance during the evaluation of geofluid reservoirs. In this study, these effects are assessed by combining synchrotron X-ray computed microtomography (SR micro-CT) and computational fluid dynamics. The studied samples pertain to deformed porous carbonate grainstones highly affected by deformation bands (DBs) exposed in Northwestern Sicily and Abruzzo regions, Italy. The high-resolution SR micro-CT images of the samples, acquired at the SYRMEP beamline of the Elettra - Sincrotrone Trieste laboratory (Italy), were used for simulating a pressure-driven flow by using the lattice-Boltzmann method (LBM). For the experiments, a multiple relaxation time (MRT) model with the D3Q19 scheme was used to avoid viscosity-dependent results of permeability. The permeability was calculated using Darcy's law once steady conditions were reached. After the simulations, the pore-network properties (effective porosity, specific surface area, and geometrical tortuosity) were calculated using 3D images of the velocity fields. These images were segmented considering a velocity threshold value higher than zero. The study showed that DBs may generate significant heterogeneity and anisotropy of the permeability of the evaluated rock samples. Cataclasis and cementation process taking place within the DBs reduce the effective porosity and therefore the permeability. Contrary to this, pressure dissolution and faulting may generate connected channels which contribute to the permeability only parallel to the DB.